2014
DOI: 10.1186/1756-3305-7-301
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection and associated risk factors in Huicholes in Mexico

Abstract: BackgroundVery little is known about the seroepidemiology of Toxoplasma gondii infection in ethnic groups in Mexico. Huicholes are an indigenous ethnic group living in a remote mountainous region in Mexico. We sought to determine the prevalence of anti-Toxoplasma IgG and IgM antibodies in Huicholes; and to determine the association of Toxoplasma seropositivity with socio-demographic, behavioral, and clinical characteristics of Huicholes.MethodsWe performed a cross sectional survey in Huicholes from September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
6
14
2
Order By: Relevance
“…Further analysis revealed that older age groups (≥ 50 years) were three times more likely to have T. gondii seroposive results than the younger age groups (≤ 24 years). This finding is consistent with the majority of studies in the world 12 , 17 , 22 , 24 . The explanation would be an enhanced exposure to toxoplasmosis by means of consumption of raw or undercooked infected products.…”
Section: Discussionsupporting
confidence: 93%
“…Further analysis revealed that older age groups (≥ 50 years) were three times more likely to have T. gondii seroposive results than the younger age groups (≤ 24 years). This finding is consistent with the majority of studies in the world 12 , 17 , 22 , 24 . The explanation would be an enhanced exposure to toxoplasmosis by means of consumption of raw or undercooked infected products.…”
Section: Discussionsupporting
confidence: 93%
“…It is unclear whether infection with T. gondii may affect the inner ear. However, dizziness -a symptom that may reflect disease in the inner ear- has been associated with T. gondii infection in the ethnic group of Huicholes [ 32 ] and in migrant agricultural workers in Durango, Mexico [ 33 ]. Further research to elucidate the role of T. gondii infection in inner ear disease is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the high seroprevalence of T. gondii exposure found in miners (60.0%) is the highest seroprevalence reported in population groups in Durango State so far. Thus, seroprevalence found in miners is higher than the seroprevalences of T. gondii infection reported in adults in rural communities in Durango State (23.8%) [10], in schizophrenic patients (20%) [14], in waste pickers (21.1%) [15], inmates (21.1%) [16], and ethnic groups living in rural communities including Tepehuanos (22.4%) [17] and Huicholes (33.2%) [18]. In addition, the seroprevalence found in miners is higher than the weighted mean (19.27%) national seroprevalence of T. gondii infection found in Mexico [19].…”
Section: Discussionmentioning
confidence: 99%